Pigmented Nodular Basal Cell Carcinomas in Differential Diagnosis with Nodular Melanomas: Confocal Microscopy as a Reliable Tool for In Vivo Histologic Diagnosis - Alice Casari; Giovanni Pellacani; Stefania Seidenari; Anna Maria Cesinaro; Francesca Beretti; Patrizia Pepe; Caterina Longo (Journal of Skin Cancer)
Nodular basal cell carcinoma, especially when pigmented, can be in differential diagnosis with nodular melanomas, clinically and dermoscopically. Reflectance confocal microscopy is a relatively new imaging technique that permits to evaluate in vivo skin tumors with a nearly histological resolution. Here, we present four cases of challenging nodular lesions where confocal microscopy was able to clarify the diagnosis.